1997
DOI: 10.1046/j.1365-2990.1997.9198091.x
|View full text |Cite
|
Sign up to set email alerts
|

Region-selective glutamine synthetase expression in the rat central nervous system following portocaval anastomosis

Abstract: Glutamine synthetase (GS) content was investigated using immunohistochemical methods in the hippocampus, cerebellum and spinal cord of rats after long-term portocaval anastomosis (PCA). Six months after surgery, GS content was increased in several areas of each region and decreased in others, compared with controls. In the hippocampus, the CA1-CA3 pyramidal subfields and the dentate molecular layer had a high level of GS expression; PCA reduced GS content in other hippocampal regions, such as the dentate hilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…There is a good number of studies on the effects of PCS on astrocytes, showing changes that are different in depending on the brain region (Bodega et al 1991; Suárez et al 1997) and on the time after PCS surgery (Ma et al 1991). In general these studies show enlarged nuclear size (Diemer and Laursen 1977), increased astrocyte cell and cytoplasmic area (Laursen and Diemer 1980) and no evidence of Alzheimer type II cells (Pilbeam et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…There is a good number of studies on the effects of PCS on astrocytes, showing changes that are different in depending on the brain region (Bodega et al 1991; Suárez et al 1997) and on the time after PCS surgery (Ma et al 1991). In general these studies show enlarged nuclear size (Diemer and Laursen 1977), increased astrocyte cell and cytoplasmic area (Laursen and Diemer 1980) and no evidence of Alzheimer type II cells (Pilbeam et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A key and specific process of astroglial function is the glutamateglutamine shuttle, which includes the uptake of the excess extrasynaptic glutamate and the production (via astroglial enzyme GS) and release from astroglia of glutamine, which is then taken up by neuronal elements to replenish the supply of glutamate (Zwingmann and Leibfritz, 2003;Hertz, 2004;Hertz and Zielke, 2004;Fonseca et al, 2005), which plays a major role in central sensitization (Dubner and Basbaum, 1994;Sessle, 2000;Woolf and Salter, 2006). In the spinal cord as well as the brain, GS exists in astroglia and oligodendrocytes but not in neurons (Norenberg, 1979;Warringa et al, 1988;Cammer, 1990;Suarez et al, 1997Suarez et al, , 2002; however, some earlier radio-assay studies reported that GS may also exist in cultured cortical neurons (Zwingmann and Leibfritz, 2003). Although there is a lack of direct evidence for altered astroglial GS activity in the spinal cord related to peripheral inflammatory events, recent studies have reported that GS activity is increased in the white and gray matters of lumbar as well as cervical enlargements 7 d after spinal cord injury in rats (Benton et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Others have found decreased GS activity and either no change or increased expression after prolonged portacaval anastomosis (Suarez et al, 1997(Suarez et al, , 2002Desjardins et al, 1999). We observed no changes in cortical GS activity or in the overall optical density of immunostained sections of cortex during 24 h of hyperammonemia.…”
Section: Gsmentioning
confidence: 95%